Zasnova Plečnikovega načrtovanja prenove Ljubljane - Jan, Andreja (Urbani izziv, 2001)
Most of Plečnik's work was achieved in the strict urban core, mainly on the edge joining the historical medieval core with the new city. Plečnik gradually created a composition of places surrounding the old city that became important connecting elements between the medieval and modern city, at that time in its firs development surge. From his work it is clear that he achieved his imaginary city gradually and methodically, with architectural emphasis and based on ties between particular key spaces in the city, tied them together with axes and merged them into present urban tissue.
Keywords: architecture; arhitektura; Ljubljana; Plečnik, Jože, 1872-1957; prenova; urbani razvoj; urbanism; urbanizem